PERLINDUNGAN HUKUM NOTARIS TERKAIT PEMALSUAN IDENTITAS DEBITOR DALAM AKAD MURABAHAH DI BSI MAKASSAR - Suharti Febriana; Ahmadi Miru; Muhammad Azwan (El-Iqthisadi, 2022)
Abstract This study aims to examine and analyze the form of responsibility for the notarys deed made related to the falsification of the debtors identity in the Akad Murabahah; and analyzing forms of legal protection for notaries regarding falsification of debtor identityes in Akad Murabahah. This research is a normative research using a statutory approach and a cese approach. The results show that legal protection for notaries for false information or identities has not been regulated in the UUJN, legal protection from the notaris honorary council MKN only approves or refuses when a notary summoned by investcth. The notarys responsibility regarding false identity or false information in making an authentic deed in akad murabahahcannot beaccounted for by a notary as long as the notary does’t violate UUJN, does’t violate the technique of making the deed, or the applicable laws. Keywords: Akad Murabahah, False identity, Notary.